The Increasing Student Motivation for Speaking Skills with MALL (Mobile-Assisted Language Learning) - Pebiana Pebiana; Desty Febria (SALEE: Study of Applied Linguistics and English Education, 2023)
MALL (mobile-assisted language learning) was implemented in order to raise pupils' grades, especially in English-speaking classes. Microsite was used to assist students in accessing learning materials. The study was carried out at one of Batam's secondary schools. Students in grade 10 of the second semester at one public high school were the subject of this study. The researchers as teachers would observe 50 science students through the evaluation in English class. To acquire data, the researchers compared pre-test and post-test results. and found out whether the strategy was successful in enhancing students' speaking abilities. Classroom action research (CAR) was applied to solve the issue in the class. The information was obtained in four steps: planning, acting, observing, and reflecting. The results revealed the speaking abilities of students have improved between pre-tests and post-tests. Students received a score of 59.56. for the average score of pre-tests and were categorized poorly. After implementing MALL (mobile-assisted language learning) activities, the average grades of the students increased. Post-tests gained 65.47 with a great improvement in several aspects such as pronunciation was 10.14% and followed by fluency was 6,3% improvement. The evidence indicates that students responded positively to the MALL (mobile-assisted language learning) method particularly when using Microsite. The findings concluded that students' enthusiasm to learn English has been enhanced by MALL (mobile-assisted language learning), which has also boosted their speaking abilities.